Large enhancements in low latitude total electron content during 15 May 2005 geomagnetic storm in Indian zone - Dashora, N.; Sharma, S.; Dabas, R.S.; Alex, S.; Pandey, R. (My University, 2009)
Results pertaining to the response of the equatorial and low latitude ionosphere to a major geomagnetic storm that occurred on 15 May 2005 are presented. These results are also the first from the Indian zone in terms of (i) GPS derived total electron content (TEC) variations following the storm (ii) Local low latitude electrodynamics response to penetration of high latitude convection electric field (iii) effect of storm induced traveling atmospheric disturbances (TAD's) on GPS-TEC in equatorial ionization anomaly (EIA) zone. Data set comprising of ionospheric TEC obtained from GPS measurements, ionograms from an EIA zone station, New Delhi (Geog. Lat. 28.42° N, Geog. Long. 77.21° E), ground based magnetometers in equatorial and low latitude stations and solar wind data obtained from Advanced Composition Explorer (ACE) has been used in the present study. GPS receivers located at Udaipur (Geog. Lat. 24.73° N, Geog. Long. 73.73° E) and Hyderabad (Geog. Lat. 17.33° N, Geog. Long. 78.47° E) have been used for wider spatial coverage in the Indian zone. Storm induced features in vertical TEC (VTEC) have been obtained comparing them with the mean VTEC of quiet days. Variations in solar wind parameters, as obtained from ACE and in the SYM-H index, indicate that the storm commenced on 15 May 2005 at 02:39 UT. The main phase of the storm commenced at 06:00 UT on 15 May with a sudden southward turning of the Z-component of interplanetary magnetic field (IMF-Bz) and subsequent decrease in SYM-H index. The dawn-to-dusk convection electric field of high latitude origin penetrated to low and equatorial latitudes simultaneously as corroborated by the magnetometer data from the Indian zone. Subsequent northward turning of the IMF-Bz, and the penetration of the dusk-to-dawn electric field over the dip equator is also discernible. Response of the low latitude ionosphere to this storm may be characterized in terms of (i) enhanced background level of VTEC as compared to the mean VTEC, (ii) peaks in VTEC and foF2 within two hours of prompt penetration of electric field and (iii) wave-like modulations in VTEC and sudden enhancement in hmF2 within 4–5 h in to the storm. These features have been explained in terms of the modified fountain effect, local low latitude electrodynamic response to penetration electric field and the TIDs, respectively. The study reveals a strong positive ionospheric storm in the Indian zone on 15 May 2005. Consequences of such major ionospheric storms on the systems that use satellite based navigation solutions in low latitude, are also discussed.
Keywords: Geomagnetic storm; Low latitude; Equatorial ionosphere; Magnetosphere interactions; Total electron content; VTEC